FATAL BRAND CRISIS: CAN BOLSTERING STRATEGY REBUILD THE TARNISHED REPUTATION? - Ahmad, Roslizawati (Journal of Technology Management and Business, 2017)
Business considers brand reputation is the key to survival for the organization. The occurrence of fatal brand crisis leaves a huge negative impact on the organization. Concurrently, brand crisis response strategy has received growing attention and the best comprehensive strategy has been increasingly emphasized. In this study, the linkages between bolstering strategy consist of reminder strategy, ingratiation strategy and victimage strategy to the brand reputation has been examined. The discussions are based on the findings from this study on the flight passengers in Northern Region of Malaysia. This study concludes with the discussion on the theoretical, practical contribution, limitation of this study and recommendations for future research.